Instructional Communication in U.S. Evangelical Christian Youth Ministries: Examining Youth Minister Perceptions. - Taylor, Lakelyn E.; Sellnow, Deanna D. (Journal of Communication & Religion)
One primary goal of youth ministry programs is to teach adolescents about a given faith and, in doing so, to foster active and ongoing lifelong engagement in spiritual life. Although youth ministry settings differ from conventional classrooms in some ways, their fundamental objective of teaching and learning is the same. In this sense, youth ministers function as "teachers" and adolescents as "students." This exploratory study examines youth ministry pedagogy via an instructional communication lens to discover the degree to which it follows what the research promotes as best practices for teaching and learning. The analysis, grounded in experiential learning theory as conceptualized in the learning cycle and IDEA model, revealed several important conclusions. Youth ministers rely primarily on teaching through lectures. When they do engage in classroom discussions, they typically employ a minister-led teacher-to-student approach. Consequently, students participate as passive learners who are presumed to absorb the information presented to them by the experts (i.e., youth ministers). Students are rarely provided opportunities to apply concepts directly to their personal life experiences beyond the classroom or to enact action steps experientially based on the material presented. Based on these findings, several implications for youth ministers and youth ministry programs, as well as suggestions for future research, are posed.